2010
DOI: 10.1186/1471-2458-10-647
|View full text |Cite
|
Sign up to set email alerts
|

CT scan screening is associated with increased distress among subjects of the APExS

Abstract: BackgroundThe aim of this study was to assess the psychological consequences of HRCT scan screening in retired asbestos-exposed workers.MethodsA HRCT-scan screening program for asbestos-related diseases was carried out in four regions of France. At baseline (T1), subjects filled in self-administered occupational questionnaires. In two of the regions, subjects also received a validated psychological scale, namely the psychological consequences questionnaire (PCQ). The physician was required to provide the subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Patients’ have been previously shown to have emotional responses to incidental nodule detection. 9–11 , 22 In addition, providers’ initial communication regarding nodule detection does affect patients’ perceptions and distress. 9 Distress of this type may lead to poor adherence with further evaluations, as has been described in the context of screening for other cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients’ have been previously shown to have emotional responses to incidental nodule detection. 9–11 , 22 In addition, providers’ initial communication regarding nodule detection does affect patients’ perceptions and distress. 9 Distress of this type may lead to poor adherence with further evaluations, as has been described in the context of screening for other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Patients experience significant distress after incidental nodule detection. 9–11 A systematic review of lung cancer screening trials, mostly from Europe, found that false positive screening results were often associated with short-term increases in distress, which returned to baseline levels over time. 8 Little is known about how patients’ emotional responses, knowledge of an incidental pulmonary nodule and the follow-up plan change over time, as well as the impact of distress.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, in mostly European screening trials, subjects with nodules report a short-term increase in distress but no change in health-related quality of life (9-12) (13). A recent study found that patients with incidental pulmonary nodules experienced significant distress after the diagnosis (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although in most screening programs for other cancers these concerns have been demonstrated to be short-lived, among asbestos-exposed workers pulmonary abnormalities including pleural plaques may be detected. A study in France documented increased stress in asbestos-exposed subjects screened by LDCT with such abnormalities detected that persisted to ≥6 months (17). Increased care may therefore be needed in asbestos-exposed workers found to have such abnormalities assuring them of the benign nature of the lesions.…”
Section: Discussionmentioning
confidence: 99%